EXPRESSION OF “PROCESSIVITY” WITHIN ENGLISH MOTION MANNER MEANINGS IN LEXICAL AND SYNTAX LAYERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The universe is a whole system consisting of a set of interconnected objects, not individual objects, events, processes. There are two distinct differences between the motion manner tools of the “process” and “ability” groups. First, a means of expressing one of the meanings in the group of “processivity” is a relatively uncommon linguistic phenomenon that means a different manner in its own right. Almost all units meaning “ability” have the property of semantic polyfunctionality. Second, the scope of lexical level, partly morphological level, and syntactic level tools, which are an integral part of the “processivity” meaning group, is limited to the scope of informal speech. In contrast, the use of lexical layer means meaning “ability” is not limited to the scope of informal speech.At the lexical level, each motion verb also includes the meaning of manner in its structure. Given that many verbs in English are formed from expressions that imitate the sound of an action, this expression further increases the number of means. At the syntactic level, motion manner meanings are expressed through various word combinations. Lexemes belonging to the case group play a role as a subordinate part of these word combinations, and this part serves to explain the manner of the main predicate.